The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/ctr.13467
|View full text |Cite
|
Sign up to set email alerts
|

Early hospital readmission after kidney transplantation under a public health care system

Abstract: Early hospital readmission (EHR) is associated with increased mortality after kidneytransplantation. This is influenced by population demographics and the comprehensiveness of the healthcare system. We investigated the incidence and risk factors associated with EHR and 1-year patient and graft survivals. Methods:We included all recipients of kidney transplant between 2011 and 2012.We excluded recipients younger than 18 years, retransplants and who died or lost the graft during the index hospital admission.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
(57 reference statements)
1
16
0
3
Order By: Relevance
“…Longer transplant admission LOS was observed more frequently in patients with ED visits and hospitalizations. Longer hospital stay was associated with an increased risk of early hospital readmissions in a study by Tavares et al 18 This prolonged LOS could be observed in the setting of DGF and also in patients with numerous comorbidities, which may necessitate a longer transplant admission. These increased LOS transplant admissions are surrogate markers for overall patient vulnerabilities and reflect their overall comorbid condition burdens.…”
Section: Discussionmentioning
confidence: 92%
“…Longer transplant admission LOS was observed more frequently in patients with ED visits and hospitalizations. Longer hospital stay was associated with an increased risk of early hospital readmissions in a study by Tavares et al 18 This prolonged LOS could be observed in the setting of DGF and also in patients with numerous comorbidities, which may necessitate a longer transplant admission. These increased LOS transplant admissions are surrogate markers for overall patient vulnerabilities and reflect their overall comorbid condition burdens.…”
Section: Discussionmentioning
confidence: 92%
“…Early hospital readmission was the most frequently reported quality metric and was noted in 26 separate publications. 18,19,24,25,42,[44][45][46]49,51,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] Patient survival was the next most frequently reported quality metric (n = 20 publications), 19,20,24,25,27,28,30,31,33,35,38,42,51,52,[71][72][73][74][75][76] followed by graft survival (n = 16 publications), 19,20,24,27,…”
Section: Frequency Of Metric Reportingmentioning
confidence: 99%
“…Patients who experience an unplanned readmission after KT have a 50% higher mortality rate than those without an unplanned readmission [ 8 ]. Unplanned readmissions not only negatively affect a patient’s physical and mental well-being, but also increase the financial burden and limits healthcare resources [ 9 ]. Therefore, reducing the unplanned readmission rate after KT is beneficial for both the patients and institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Nationally, the incidence rate of unplanned readmissions after KT within 30 days ranges from 20.6% to 45% [ [10] , [11] , [12] ], a substantially higher rate than for patients undergoing other surgeries (4%–15%) [ 13 ]. Prior studies have identified several risk factors for the 30-day readmission rate, such as recipient age, comorbid diabetes mellitus, length of stay, cytomegalovirus (CMV) serology negative, deceased kidney donation, delayed graft functioning and low glomerular filtration rate at discharge [ 9 , 14 , 15 ]. However, these studies focused on the short term [ [16] , [17] , [18] , [19] ], with a lack of long-term follow-up data.…”
Section: Introductionmentioning
confidence: 99%